The protein and peptide fractions of kashk, a traditional Middle East fermented dairy product. (June 2020) - Pourjoula, Mina; Picariello, Gianluca; Garro, Giuseppina; D'Auria, Giovanni; Nitride, Chiara; Rheza Ghaisari, Amid; Ferranti, Pasquale
Graphical abstract: Highlights: Foodomics was applied to the study of peptidome of kashk, a Middle East fermented dairy product. The analysis allowed identifying the pathways of protein and peptides during kashk production. Potentially bioactive peptides are produced during fermentation and maturation. In vitro digestion showed a high digestibility and survival of bioactive amino acid sequences. Abstract: Kashk is a typical dairy product of Iran, made from sour milk. It is traditionally produced from buttermilk in a dry, round-shaped form. Today, it is also produced at industrial level in a liquid form starting from fermented milk. We aimed to characterise the kashk proteome and peptidome comparing a traditional product with the industrial using a combination of proteomic approaches including advanced chromatographic and electrophoretic separation technique coupled to tandem mass spectrometry. We identified also phosphorylated casein-derived peptides (CPP) and investigated kashk protein digestibility using a static model of food protein digestion. The molecular characterization, coupled with bioinformatic in silico analysis, allowed the identification of potential bioactive peptides.